IMPLEMENTASI KERJASAMA INDONESIA DAN PORTUGAL DALAMMENGURANGI TINGKAT PENYALAHNGUNAAN DAN KEMATIAN AKIBATNARKOBA DI INDONESIA 2014-2019 - Dinda Alifia Jipining Harfiwi (2020)
Narcotics circulation in Indonesia is still very high due to geographical and cultural factors or Indonesia in Indonesia which causes narcotics circulation to increase. Drug dealers and drugs are once again among the community before the previous community. Increasing distribution will increase if it is not eradicated, and more claims will be made. This is the urgency of Indonesia to collaborate, namely cooperation with Portugal. Because Portugal is considered capable of being a partner of Indonesia and Portugal is a country that is able to support the drug and its distribution. So the transfer of memorandum of understanding between Indonesia, BNN as a representation with Portugal, SICAD as a representation to collaborate in 2014. Many programs are run and implemented to implement it. This study discusses the implementation of cooperation carried out by Indonesia and Portugal for members of the narcotics distribution and social reintegration for drug addicts to be accessible for the social environment. The research method used in this study is a qualitative research method with analytical research supported by International Cooperation theory and the concept of Transnational Crime. The final results of this study will discuss and show the various programs implemented during the course of the collaboration, the results generated by these programs and their constraints,